Corpses for Beginners (KULT_online, 2011)
The anthology Objekt Leiche (Object Corpse) focuses on the appropriation of dead bodies in different contexts. Papers from research areas such as history, sociology, psychology, and literature chiefly present an historical overview. Their main interest is in the actual proceedings (and attendant rationales) which accompany burial, presentation, and commemoration from ancient burial rituals to the virtual cemeteries and exhibitions of plasticized bodies of the present day.